The Milesian School: the Relationship between Religion and Philosophy - Degutis, Mykolas (Literatūra, 2025)
This article proposes an interpretation of the fragments of the Milesian thinkers which aims to demonstrate the compatibility of their thought with the Greek religious tradition. The concept of the first principle denotes a shared discourse between philosophers and poets, both of which focused on elucidating the origin or essence of the cosmos. From this common discourse, the Milesians develop a unique perspective on religion, exemplified by the suggested reading of Thales’ dictum ‘everything is full of gods’: it is argued that the dictum criticises the common popular view of the gods. By acknowledging this critical Milesian perspective on the gods, we can also analyse other Milesian fragments in a new light thus disclosing their inclination to perceive the gods via an ontological lens.